Murine Leukemia Viruses: Objects and Organisms - Alan Rein (Advances in Virology)
Murine leukemia viruses (MLVs) are among the simplest retroviruses. Prototypical gammaretroviruses encode only the three polyproteins that will be used in the assembly of progeny virus particles. These are the Gag polyprotein, which is the structural protein of a retrovirus particle, the Pol protein, comprising the three retroviral enzymes—protease, which catalyzes the maturation of the particle, reverse transcriptase, which copies the viral RNA into DNA upon infection of a new host cell, and integrase, which inserts the DNA into the chromosomal DNA of the host cell, and the Env polyprotein, which induces the fusion of the viral membrane with that of the new host cell, initiating infection. In general, a productive MLV infection has no obvious effect upon host cells. Although gammaretroviral structure and replication follow the same broad outlines as those of other retroviruses, we point out a number of significant differences between different retroviral genera.